2005
DOI: 10.1016/j.molcel.2005.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Lysine 9 Methylation and HP1γ Are Associated with Transcription Elongation through Mammalian Chromatin

Abstract: Methylation of histones modulates chromatin structure and function. Whereas methylation of histone H3 on lysines 4, 36, and 79 has been linked with gene activation, methylation of H3 on lysines 9 and 27 and histone H4 on lysine 20 is associated with heterochromatin and some repressed genes within euchromatin. Here, we show that H3K9 di- and trimethylation occur in the transcribed region of active genes in mammalian chromatin. This modification is dynamic, as it increases during activation of transcription and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

63
548
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 651 publications
(616 citation statements)
references
References 49 publications
(5 reference statements)
63
548
3
2
Order By: Relevance
“…In addition to its physical association with RNA polymerase II, Vakoc et al (2005) confirmed the presence of H3K9Me3 within heterochromatic major satellite repeats. H3K9Me3 modifications may be unique among histone methylation modifications in being associated with both heterochromatin and actively transcribed genes (Eissenberg and Shilatifard, 2006).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In addition to its physical association with RNA polymerase II, Vakoc et al (2005) confirmed the presence of H3K9Me3 within heterochromatic major satellite repeats. H3K9Me3 modifications may be unique among histone methylation modifications in being associated with both heterochromatin and actively transcribed genes (Eissenberg and Shilatifard, 2006).…”
Section: Discussionmentioning
confidence: 68%
“…This observation seems at variance with the well described association of H3K9Me3 with both constitutive (Peters et al, 2003) and facultative heterochromatin (Heard et al, 2001). Vakoc et al (2005) further reported that heterochromatin protein 1g (HP1g), which contains a chromo-domain predicted to recognize H3K9 methylation, is also present in the transcribed region and may form a complex with RNA polymerase II. Importantly, they demonstrated the specificity of the antibodies they used in their chIP experiments and ruled out cross-reactivity of H3K9Me3 with other markings that could have produced spurious results.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations